Perbedaan perspektif pendidikan agama dalam menurut teologi islam dan teologi barat - Nasikhin Nasikhin; Shodiq Shodiq (Jurnal Al-Fatih, 2021)
This study aims to examine the differences in the concept of religious education in the perspective of Islamic theology and the Western world. This study uses qualitative research methods to explore information related to the central theme of theology in religious Education. From the results of the analysis that has been carried out, it is obtained that research data shows that the western model of education does not have space for the conception of God will, God pleasure, the conception of human servitude to God, let alone the conception of post-world life. The Western view is more concerned with human-centric interests without trying to relate it to the intervention of the Ultimate Reality. This causes education to lead people to become materialistic, hedonistic, pragmatic, and sometimes fall into the atheistic valley. As a result, the existence of the psyche, credo, and spirituality is not touched, so that humans become worried, restless, and restless due to the worship of the results of human thought. While education from an Islamic point of view, especially that which is supported by theological understanding, provides enlightenment for educational problems. Islam does not mean that it does not optimally view human abilities, but behind all that the achievement of human progress as a result of the educational process remains in the corridor of God relationship and involvement.